L’Unione Europea tra rivoluzione passiva e questione meridionale. Note a partire da Gramsci - Diego Fusaro (Rosenberg & Sellier, 2015)
This essay examines the economic and political conditions and the balance of power in today’s European Union. It does this by using some of the categories of Antonio Gramsci’s ‘Prison Notebooks’, in particular the concept of ‘southern question’, the ‘passive revolution’ and the ‘Caesarism’. The aim is to criticize the ‘European system’ trough a perspective that, recalling Gramsci, gives emphasis on labor Issues and ‘subordinates’.